Analysis of Fishermen Insurance Need Levels to increase Well-Being in Sekaya Maritim Bontoa District Maros Regency - Rahmat, Awaluddin; Alwi, Muh. Jamal; Danial, Danial (FAPETKAN UNTAD, 2019)
This study aimed to determine the level of need and mechanism of fishermen insurance in sekaya maritim, as well as to find out the impacts that arise and strategies for developing fishermen insurance, thus it can be felt by other fishing communities. Data collection were carried out by literature study and field studies through interviews, observation and documentation. Sampling was done with a purposive sampling method with total of 70 respondents. The results showed that several factors that caused the importance of fishermen's insurance needs were the number of family members, the age of the fisherman, and the working hours of fishermen. Fishermen who have fulfilled the requirements for Fishermen Premise Insurance Assistance (Bantuan Premis Asuransi Nelayan/BPAN) are given an Insurance Card and Realization Policy. A total of 8 fishermen families have received insurance, hence they can improve their economic condition. The fishermen insurance development strategy is that fishermen who have met the insurance participant requirements can enjoy the benefit of insurance every year.Keywords: Fishermen insurance, Sekaya maritim, Development strategy.